2009
DOI: 10.1111/j.1570-7458.2009.00930.x
|View full text |Cite
|
Sign up to set email alerts
|

Mate‐finding failure as an important cause of Allee effects along the leading edge of an invading insect population

Abstract: The movement of humans and goods has facilitated the arrival of non‐native insects, some of which successfully establish and cause negative consequences to the composition, services, and functioning of ecosystems. The gypsy moth, Lymantria dispar (L.) (Lepidoptera: Lymantriidae), is currently invading North American forests at variable rates, spreading by local and long‐distance movement in a process known as stratified dispersal. Newly arriving colonizers often occur considerably ahead of the population front… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 67 publications
0
74
0
Order By: Relevance
“…Although originally described by Baker as equally applicable to both animal and plant populations, most references to Baker's law come from the plant literature. Given that pest species are often well studied (and have in some cases been clearly shown to suffer from matefinding Allee effects; Contarini et al 2009;Yamanaka and Liebhold 2009), it is intriguing how few studies contrast different eradication techniques depending on the mating system (see Yamanaka and Liebhold 2009 for a rare example), and we are unaware of such contrasts that have also included dispersal behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although originally described by Baker as equally applicable to both animal and plant populations, most references to Baker's law come from the plant literature. Given that pest species are often well studied (and have in some cases been clearly shown to suffer from matefinding Allee effects; Contarini et al 2009;Yamanaka and Liebhold 2009), it is intriguing how few studies contrast different eradication techniques depending on the mating system (see Yamanaka and Liebhold 2009 for a rare example), and we are unaware of such contrasts that have also included dispersal behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties in finding mates can cause an Allee effect, where population growth decreases at low densities (Stephens et al 1999). As low densities are typically encountered at the edge of a population's range, Allee effects (due to mate finding and other causes) are likely to be an important factor in determining the rate of spread of sexually reproducing species, with the potential to slow down the rate of spread or even prevent invasions (Lewis and Kareiva 1993;Veit and Lewis 1996;South and Kenward 2001;Taylor and Hastings 2005;Robinet et al 2008;Contarini et al 2009;Krkošek et al 2012). Recent models (Miller et al 2011), together with experimental work (Miller and Inouye 2013), have shown that sex-specific differences in demographic and dispersal parameters alone (ignoring the added complication of demographic Allee effects or dispersal evolution) can drastically influence the spread rate of a population.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, an intermediate rather than maximal signaling effort can still be selected for, if high signaling effort is costly. Such costs can be difficult to detect precisely because females are not typically expected to evolve highly costly mate acquisition traits (Kokko and Wong 2007), but it is noteworthy that (1) costs can shape mating systems even if they are small or (2) sometimes sperm limitation can make females evolve costly mate acquisition traits (for insect data, see Charlat et al 2007;Calabrese et al 2008;Rhainds 2010; for data from spatially varying situations, see Contarini et al 2009;Rhainds 2012). Accordingly, we now assume that multiple male arrivals are not costly (we modify the above model to have k ≥ 1) and include direct costs of pheromone production.…”
Section: Balancing Mate Arrival Rate With Increasing Costs Of Callingmentioning
confidence: 99%
“…Virgin females are unlikely to have precise information about the likelihood of encounters with potential mates, which tends to vary spatially (Robinet et al 2008;Contarini et al 2009) and temporally (Calabrese and Fagan 2004;Rhainds 2012). Even if male density were constant, there is inherent unpredictability in whether male flight paths cross female pheromone plumes.…”
Section: A Theoretical Approach To Adaptive Variation In Female Pheromentioning
confidence: 99%
“…Such an Allee effect would also constrain northward expansion of bagworm populations even if environmental conditions were to ameliorate and allow colonization and persistence in more northerly locales. Researchers studying gypsy moths, another lepidopteran pest species with flightless females, have demonstrated the critical roles that Allee effects play in the establishment and persistence of nascent populations (Vercken et al 2011) and in determining the species' overall rate of spatial spread (Johnson et al 2006, Contarini et al 2009). Additional data on populations at the bagworm's range boundary and, if possible, populations experimentally introduced north of the boundary, are needed to identify what density and spatial distribution of peripheral populations are sufficient for successful mating and population persistence.…”
Section: Key Research Needsmentioning
confidence: 99%